2015
DOI: 10.1039/c5fo00367a
|View full text |Cite
|
Sign up to set email alerts
|

Yeast with bacteriocin from ruminal bacteria enhances glucose utilization, reduces ectopic fat accumulation, and alters cecal microbiota in dietary-induced obese mice

Abstract: YB resulted in body weight loss, promoted lipid catabolism and carbohydrate utilization; it also modulated cecal microbiota, and therefore partially improved the health of obese mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In addition, studies have shown that gut microbiota impact significantly on the relative composition and abundance of bile acids across multiple body compartments, and an elevation of serum bile acids shows a significantly increased risk for intrauterine fetal death ( Geenes et al., 2014 , Rezai et al., 2015 , Swann et al., 2011 ). Tsai et al. (2015) also reported that LY could contribute to the regulation of bile acids metabolism in diet-induced obese mice.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, studies have shown that gut microbiota impact significantly on the relative composition and abundance of bile acids across multiple body compartments, and an elevation of serum bile acids shows a significantly increased risk for intrauterine fetal death ( Geenes et al., 2014 , Rezai et al., 2015 , Swann et al., 2011 ). Tsai et al. (2015) also reported that LY could contribute to the regulation of bile acids metabolism in diet-induced obese mice.…”
Section: Discussionmentioning
confidence: 94%
“…Escherichia are considered to serve an important function in the mechanism of glycolytic pathways for regulating glucose catabolism ( 15 ). Previous studies have demonstrated that decreased relative abundance of Akkermansia and increased relative abundance of Bacteroides , Ruminococcus and Parabacteroides in the gut microbiome can improve glucose homeostasis in obese mice and provide a catabolic pathway through a novel mannosylglucose phosphorylase, suggesting that Akkermansia , Bacteroides , Ruminococcus and Parabacteroides may serve an important function in the mechanism of glycometabolism ( 16 19 ). There appears to be a significant enrichment of Megamonas in Chinese people compared with other ethnicities, and it may serve a potential glycometabolism role ( 20 ).…”
Section: Discussionmentioning
confidence: 99%